Pakatan Harapan's Performance in the 2021 Sarawak State Election - Ivy, Jugah; Hafizan, Mohamad Naim (Penerbit Universiti Sains Malaysia, 2024)
This article aims to examine the performance of Pakatan Harapan (PH) in the 2021 Sarawak State Election (SSE21). It explains the three main reasons for PH’s dismal showing. First, local-based political parties took advantage of structural weaknesses in Sarawak PH and managed to convince Sarawakians that state rights could only be protected by political entities controlled by Sarawak leaders. Second, the “Sarawak First” sentiment changed the political landscape of Sarawak and increased the sense of solidarity among Sarawakians. It was the driving force behind the campaign messages of the local-based political parties that resonated well among the majority of the Sarawakian voters. Third, the three PH coalition parties in Sarawak, namely Democratic Action Party (DAP), Parti Keadilan Rakyat (PKR) and Parti Amanah Negara (AMANAH) did not have a common political ideology to bind them together, strengthening the common belief that DAP, PKR and AMANAH came together simply out of convenience to gain power. In order to survive in Sarawak, PH needs to rebuild its image and political strategies relevant to the needs of the Sarawakians voters. This article is based on data from online media sources and observations made during the election on 18 December 2021.